Theophylline and gastric emptying in very low birthweight neonates: a randomised controlled trial. Issue 4 (21st June 2004) - Gounaris, A; Kokori, P; Varchalama, L; Konstandinidi, K; Skouroliakou, M; Alexiou, N; Costalos, C
Abstract : Background: Theophylline treatment causes side effects such as tachycardia, hyperglycaemia, abdominal distension, and vomiting. The latter two are probably the result of delayed gastric evacuation. Objective: To study the effect of theophylline on gastric emptying time in preterm infants. Patients: The subjects were 18 premature neonates with a mean (SD) birth weight of 1302 (240) g and a mean (SD) gestational age of 28.7 (1.9) weeks. Main outcome measures: In each case, gastric emptying was measured on two occasions: once when the newborns were being treated with theophylline and once when they were not. Half of the cases were randomised to receive theophylline before the initial measurement. The opposite was applied for the rest. Gastric emptying was assessed ultrasonically by measuring the change in antral cross sectional area (ACSA) at regular intervals over 120 minutes. Results: The mean (SD) ACSA half time in the newborns receiving theophylline was 52 (19) minutes compared with 37 (16) minutes in those not receiving theophylline. This difference is significant (p < 0.05). Conclusions: Treatment with theophylline seems to delay gastric emptying in very low birthweight neonates, and this must be taken into consideration when this drug is used to treat apnoea of prematurity.